Effect of tillage and residue management on soil physical properties and crop productivity in maize (Zea mays)–Indian mustard (Brassica juncea) system - SAHA, S; CHAKRABORTY, D; SHARMA, A R; TOMAR, R K; BHADRARAY, S; SEN, U; BEHERA, U K; PURAKAYASTHA, T J; GARG, R N; KALRA, N (The Indian Journal of Agricultural Sciences, 2010)
Field experiments were carried out on a sandy loam (Typic Haplustept) soil in semi-arid climate of New Delhi to evaluate the effect of tillage (conventional and zero) and residue management (incorporation, retention and removal) on soil physical properties vis-à-vis plant growth after 3 years of continuous maize (Zea mays L.)–Indian mustard [Brassica juncea (L.) Czern. & Coss.] sequence. Maize (July–October) and mustard (October–November) were grown with conventional (disc plowing, followed by 2 cultivators) and zero tillage (no plowing) and crop residues were applied at sowing @ 3 tonnes/ha for maize and 2 tonnes/ha for mustard. Residue incorporation significantly (P<0.05) lowered the bulk density of surface (0–0.15 m) soil layer. Zero tillage with residue retention recorded significantly higher soil organic carbon and microbial biomass carbon, and also mean weight diameter and geometric mean diameter of soil aggregates. Though a compact zone (>2 MPa soil resistance) between 0.3 and 0.4 m in the profile was observed in all the plots, residue incorporation reduced the soil resistance to penetration at surface (0–0.15 m). Zero tillage resulted in higher infiltration rates, initial as well as steady state (0.120 and 0.029 m/hr where residue retained; 0.108 and 0.028 m/ hr where residue removed). Seedling emergence rates were faster in zero-tilled plots without residue for maize and mustard crops, but the quick emergence could not be effectively transformed in producing more biomass or yield. Increase in leaf area was faster under conventionally-tilled plots with residue incorporation, and the peak leaf area index was also the maximum (3.37 and 5.60 in maize and mustard, respectively). Biomass at maturity differed significantly between conventional and zero tillage, but no difference was observed between residue management practices within same tillage system. Root weight density in maize was significantly higher in conventional tillage with residue incorporation, though at deeper depths, the differences were mostly insignificant. In mustard also, maximum root weight was obtained under conventional tillage with residue incorporation. Although zero tillage optimized water use by 14 and 12% in maize and mustard, respectively as compared to conventional tillage, maximum water-use efficiency was obtained in conventional tillage with residue incorporation, mainly because of maximum yield in maize (2.93 tonnes/ ha) and mustard (1.83 tonnes/ha) obtained under the treatment.